2003
DOI: 10.1002/ajhb.10236
|View full text |Cite
|
Sign up to set email alerts
|

Binary and microsatellite polymorphisms of the Y‐chromosome in the Mbenzele pygmies from the Central African Republic

Abstract: This study analyzes the variation of six binary polymorphisms and six microsatellites in the Mbenzele Pygmies from the Central African Republic. Five different haplogroups (B2b, E(xE3a), E3a, P and BR(xB2b,DE,P)) were observed, with frequencies ranging from 0.022 (haplogroup P) to 0.609 (haplogroup E3a). A comparison of haplogroup frequencies indicates a close genetic affinity between the Mbenzele and the Biaka Pygmies, a finding consistent with the common origin and the geographical proximity of the two popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…demic diffusion and replacement, at least partially, of hunter-gatherers gene pools). Indeed, this observation is supported by mitochondrial DNA (Chen et al, 2000;Destro-Bisol et al, 2004) and Y-chromosome (Knight et al, 2003;Coia et al, 2004) analyses, which have reported a number of deep-rooting lineages shared by Pygmy (particularly Western Pygmies) and Khoisan populations. If natural selection has been the main force leading to the observed genetic affinities of both groups, one must invoke a selective advantage of the fast acetylator status (either by recent positive selection or by long-standing balancing selection) in populations with a hunter-gatherer lifestyle.…”
Section: Discussionmentioning
confidence: 54%
“…demic diffusion and replacement, at least partially, of hunter-gatherers gene pools). Indeed, this observation is supported by mitochondrial DNA (Chen et al, 2000;Destro-Bisol et al, 2004) and Y-chromosome (Knight et al, 2003;Coia et al, 2004) analyses, which have reported a number of deep-rooting lineages shared by Pygmy (particularly Western Pygmies) and Khoisan populations. If natural selection has been the main force leading to the observed genetic affinities of both groups, one must invoke a selective advantage of the fast acetylator status (either by recent positive selection or by long-standing balancing selection) in populations with a hunter-gatherer lifestyle.…”
Section: Discussionmentioning
confidence: 54%
“…Various ethnic groups from Mozambique [49 E‐M2 chromosomes, 7 STR loci (Pereira et al, )]; 14. Mbenzele Pygmies [28 E‐M2 chromosomes, 6 STR loci (Coia et al, )]; 15. 11 ethnic groups from Tanzania [93 E‐M2 chromosomes, 8 STR loci (Tishkoff et al, )]; 16.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, data have shown that the inferred ancestors of modern Pygmy hunter-gatherers and Bantu-speaking agriculturalists could have diverged as long as 70 kya [49], and that ancestral western and eastern Pygmy populations separated more than 18 kya [48] with subsequent genetic differentiation among the western Pygmies within the past 2,800 years [50]. The subtle structure among western Pygmies may be due to recent geographic isolation, genetic drift, and differential levels of admixture between Pygmies and neighboring Bantu-speaking populations [18, 49, 50, 5254]. Overall, these patterns of genetic and phenotypic variation suggest that African populations have maintained a large and subdivided population structure throughout much of their evolutionary history.…”
Section: Population Structurementioning
confidence: 99%